BOOK REVIEW OF JUSTICE A PHILOSOPHICAL BOOK OF MICHAEL J. SANDEL - Larasati, Hestiana (LANTERN (Journal on English Language, Culture and Literature), 2016)
People often seek for philosophical ideas to justify what they believe as the right thing to do. Many people believe that philosophical ideas matter to enrich their knowledge in order for them to think more wisely. It is why many books of philosophy are nowadays out to fulfill the demand from the society. Even if, many sources are also available to meet the people‟s interest in philosophy such as reading articles, watching movies and many other, average reasonable people would rather to choose to read books as their source to get philosophical idea. It is also the reason why today we have many philosophical books traded in the market and we can find them easily in many book stores, like Solitude, Voltaire, and etc.